Iklan Audio Sprite versi Bercocok Tanam dan Persepsi Penyandang Disabilitas Netra - Wijaya, Evan Timothy; Sukendro, Gregorius Genep (Prologia, 2023)
Advertising is a form of communication in which the recipient receives stimulation from the advertisement, the perception of persons with visual disabilities towards an advertisement is influenced by the interpretation of the "visual" insight they imagine. Advertising is basically a strategy in which the message should be absorbed slowly with the hope that the advertisement can bring awareness, even become top of mind. Perceptions of persons with visual disabilities towards advertisements with their respective interpretations. This study aims to understand whether their perception of an advertisement can influence the advertising message. Perception analysis in this study in this study, should be able to understand how to present advertisements that are effective for people with visual disabilities. The message obtained is relevant. With the physical disturbance that occurs, the inability of people with visual disabilities to visualize, they can still imagine the advertisement that is presented even though there is interference, message distortion that occurs, the confusion that exists actually strengthens the message of the message. Basically, advertisements will always target large market segments because the capital spent in making advertisements is not small. Even though the advertisements are not aimed directly at certain people with disabilities, the segmentation is not intended to discriminate but indirectly the hope is that smaller segmentation will get relevance to the advertisements served. In this study the authors used qualitative research methods at the Bina Netra Cahaya Bathin Social Institution and the Mardi Wuto Social Agency. From the five sources with various age groups, there is a conclusion that the advertisement succeeded in deceiving and confusing friends with visual disabilities. Then they expect narrative ads that are clearly packaged and to the point. In the end, this Sprite advertisement can still be understood by those with strong auditory sensitivity even though their sight cannot be used. Iklan merupakan bentuk komunikasi di mana penerimanya menerima rangsangan dari iklan tersebut, persepsi penyandang disabilitas netra terhadap sebuah iklan dipengaruhi oleh interpretasi wawasan “visual” yang mereka imajinasikan. Iklan pada dasarnya merupakan strategi di mana hendaknya pesan tersebut dapat diserap dengan perlahan dengan harapannya iklan dapat menghadirkan awareness, bahkan menjadi top of mind. Persepsi penyandang disabilitas netra terhadap iklan dengan interpretasinya masing-masing. Penelitian ini bertujuan memahami apakah persepsi mereka terhadap sebuah iklan dapat berpengaruh terhadap pesan iklan. Analisis persepsi dalam penelitian ini pada penelitian ini, hendaknya dapat memahami tentang bagaimana penyajian iklan yang efektif bagi penyandang disabilitas netra. Pesan yang didapatkan apakah menjadi relevan. Dengan adanya gangguan fisik yang terjadi, ketidakmampuan penyandang disabilitas netra memvisualisasikan, mereka tetap bisa membayangi iklan yang disajikan walaupun terjadi gangguan, distorsi pesan yang terjadi, kebingungan yang ada justru memperkuat pesan dari pesan itu. Pada dasarnya, iklan akan selalu menyasar segmentasi pasar yang besar karena modal yang dikeluarkan dalam pembuatan iklan tidak kecil. Walaupun iklan tidak tertuju langsung bagi kaum penyandang disabilitas tertentu, segmentasi bukan bertujuan mendiskriminasi melainkan secara tidak langsung harapannya segmentasi yang lebih kecil mendapatkan relevansi terhadap iklan yang disajikan. Pada penelitian ini penulis menggunakan metode penelitian kualitatif di Panti Sosial Bina Netra Cahaya Bathin dan Badan Sosial Mardi Wuto. Dari kelima narasumber dengan berbagai kalangan usia, terdapat sebuah kesimpulan bahwa iklan tersebut berhasil menipu dan membuat bingung teman-teman penyandang disabilitas netra. Kemudian mereka mengharapkan iklan naratif yang dikemas dengan jelas dan tidak bertele-tele. Pada akhirnya, iklan Sprite ini tetap bisa dimengerti oleh mereka dengan kepekaan indra pendengaran yang kuat walaupun tidak dapat indra penglihatan mereka tidak dapat digunakan